In vitro assays for repellents and deterrents for ticks: differing effects of products when tested with attractant or arrestment stimuli - McMahon, Conor; Kröber, Thomas; Guerin, Patrick (My University, 2003)
Most in vivo and in vitro tests with repellents or deterrents against ticks have not considered which sensory channel is being targeted. We have recorded the responses of two hard tick species (Acari: Ixodidae) in vitro to determine if such products can disrupt the perception of an attractant in a repellent assay or the perception of an arrestment stimulus in a deterrent assay. Ethyl butylacetylaminopropionate (EBAAP), N,N-diethyl-methyl-benzamide (deet), permethrin and indalone were chosen to test their capacity to inhibit the attraction of Amblyomma variegatum Fabricius to its aggregation-attachment pheromone. Vapours of each test product plus those from a synthetic blend of the pheromone were delivered to the walking tick in an air stream on a locomotion compensator. Neither EBAAP, deet, permethrin nor indalone could inhibit attraction of A. variegatum even when each of the test products was delivered at 106 times the pheromone. Indalone did decrease the attraction of A. variegatum to the pheromone and induced repulsion of A. variegatum when presented on its own in the air stream. The effect of permethrin, a sodium channel blocker, was also tested in a deterrent assay measuring the arrestment of Ixodes ricinus (L.) adults on its own faeces and faecal constituents. Permethrin deterred arrestment at doses of 670 fg/cm2 to 67 ng/cm2, i.e. at levels five times lower than the dose of chemostimuli present in the arrestment stimulus. This sensitivity to permethrin suggests that it acts via the contact chemoreception channel.
Keywords: Amblyomma variegatum; Ixodes ricinus; Ixodidae; attraction; butopyronoxyl; deet; N; N-diethyl-methyl-benzamide; deterrent; ethyl butylacetylaminopropionate; indalone; permethrin; repellent; tick